Wherewith They Weave a Paradise: Keats and the Luscious Poem - Tontiplaphol, Betsy (Romanticism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractWhen Wordsworth and Coleridge occupy scanty plots and lime-tree bowers, they do so briefly and out of necessity, but Keats consistently describes islands, burrows, bedrooms, and pavilions dense with leafy and/or commercial luxury. More important, he posits such spaces as models for good verse, which, he contends, should feel “like a little copse.” To describe Keats’s regard for packed luxury (that is, circumscribed sensory excess), I choose the term luscious, a word whose etymological links to lush, plush, delicious, lascivious, and, of course, luxurious, render it uniquely suited to an aesthetic defined, paradoxically, by great (sensory) wealth in little space. The following essay argues that this un-Wordsworthian turn to crowded interiors represents not only a Keatsian thematic preoccupation but also, perhaps counterintuitively, Keats’s most significant formal legacy. Keats’s early connection to Leigh Hunt affiliates him with the luxury-loving bourgeoisie. However, less interested in domestic spaces than poetic ones, Keats rediscovered and redefined the catalogue, or poetic list, in an effort to translate gracious living into luscious verse.